Análise do desperdício na dispensação dos medicamentos antimicrobianos na atenção primária: uma abordagem sobre o benefício do fracionamento - Santos, Willian Couto (2021)
Introduction: The fractionation of medicines is a strategic tool that aims to provide the rational use of drugs (RUD), as it allows the dispensation of the exact number of pharmaceutical units (PU) according to the prescription made by the qualified professional. However, the industries do not supply, in most of their products, fractionated packaging. Objectives: To analyze the waste of antimicrobials for systemic use in the city of Guarulhos / SP. Methodological Procedures: This is an exploratory descriptive documentary research with quantitative analysis. For this purpose, the 2nd copies of the pharmacological prescriptions for antibiotics were used, which were retained at the UBS Nova Bonsucesso pharmacy, of UBS Nova Bonsucesso, located in Guarulhos, in the period from 01/09/2020 to 10/30/2020. With these data we estimate the amount of medicine wasted and the financial loss of the municipality in relation to these drugs. The data underwent descriptive analysis of the following variables, with the help of Microsoft® Excel and Minitab® Statistical Software: relative and absolute frequency, mean and 95% confidence interval. Results: 483 antimicrobial prescriptions were analyzed, of which, 29% were amoxicillin 500mg, 31% were azithromycin 500mg, 15% were cephalexin 500mg, 12% were ciprofloxacin 500mg, 3% were clarithromycin 500mg, 2% clindamycin 300mg and 8% metronidazole 250mg. The overall waste in the dispensation represented 59.6% (95% CI = 55.3 - 64.0%), which corresponds to 288 of the studied prescriptions. 1003 PU were wasted, corresponding to R $ 418.71 (US $ PPP 187.67). Waste occurred in 29.7% of metronidazole 250mg requirements, 23.3% cephalexin 500mg, 20.5% ciprofloxacin 500mg, 12.4% azithromycin 500mg, 5.9% amoxicillin 500mg, 5% clarithromycin 500mg and 3.2% 300mg clindamycin. Regarding antimicrobials, there was waste with all of them in some observed dosage. The projected estimate for the municipality was 186,013 PU with a monthly loss amount of R$ 74,022.67 (US $ PPP 32,942.79), accumulating an annual loss of 2,232,156 PU with an annual value of R $ 888,272.04 ($ PPP 395,323.56). Final Considerations: In this context, the fractionation of drugs proved to be a strategy that would allow managers to better manage health resources, optimizing the process and making it possible to reduce the waste of antimicrobials.